MiR-3178 inhibits cell proliferation and metastasis by targeting Notch1 in triple-negative breast cancer. Issue 11 (November 2018) - Kong, Peng; Chen, Lie; Yu, Muxin; Tao, Jing; Liu, Jiawei; Wang, Yue; Pan, Hong; Zhou, Wenbin; Wang, Shui
Abstract Triple-negative breast cancer (TNBC) has a poorer outcome than other subtypes of breast cancer, and the discovery of dysregulated microRNA (miRNA) and their role in tumor progression has provided a new avenue for elucidating the mechanism involved in TNBC. In this study, we identified that miR-3178 was significantly reduced in TNBC, and the low miR-3178 expression correlated with poor overall survival in TNBC but not in non-TNBC. The ectopic overexpression of miR-3178 suppressed TNBC cell proliferation, invasion, and migration by inhibiting the epithelial-to-mesenchymal (EMT) transition. Notch1 was validated as the direct target gene of miR-3178, which was confirmed by the dual-luciferase reporter assay. miR-3178 decreased the expression of Notch1 and restoration of Notch1 expression attenuated the inhibitory effects of miR-3178 on cell proliferation, metastasis, and the EMT in TNBC. miR-3178 inhibited cell proliferation and metastasis by targeting Notch1 in TNBC, and the restoration of miR-3178 might be a potential therapeutic strategy for TNBC.